Secondary School Teachers’ Perspectives on Recent Curriculum Reform in South Sumatera: Resources and Demographic Influences - Ardiansyah, Welly; Gustiani, Sri; Aryanti, Nurul; Duyanh, Nguyen Pham (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2026)
Curriculum reform remains a central strategy for improving educational quality; however, its success largely depends on teachers’ perspectives and readiness to implement reform. This study investigates the perspectives of Indonesian secondary school teachers in South Sumatra regarding recent curriculum reforms, identifies the resources that influence these perspectives, and examines the role of demographic characteristics. Employing a quantitative cross-sectional survey design, data were collected from 342 secondary school teachers using a structured questionnaire. Analyses included descriptive statistics, Pearson correlation, independent samples t-tests, one-way ANOVA, post-hoc Tukey HSD tests, and multiple regression. The findings indicate that teachers hold moderately positive but cautious perspectives toward curriculum reform (M = 3.47). Teachers strongly acknowledge the necessity of curriculum reform, yet express reservations regarding implementation challenges and the adequacy of support and resources. Correlation and regression analyses reveal that adequate training, administrative support, and resource availability significantly and positively influence teachers’ perspectives, collectively explaining 52.3% of the variance. Demographic analyses show urban teachers report more positive perspectives than rural ones, while early-career teachers hold more favorable views than their more experienced counterparts. Overall, the results suggest that teachers are not resistant to curriculum reform; rather, their perspectives are shaped by the extent of institutional support, professional learning opportunities, and contextual conditions. The study highlights the need for sustained professional development, strong school leadership, and equitable resource distribution, particularly in rural schools, to ensure effective curriculum implementation.